Addition of L-Glutamine + Glutamic Acid and L-Arginine to the diet of weaned piglets - SILVA,DAVID R.P. DA (2022)
Abstract This study aimed to evaluate the supplementation of L-glutamine + glutamic acid and/or L-arginine on the productive performance, incidence of diarrhea, intestinal morphological of weaned piglets. Sixty-four 28-day-old weaned piglets were distributed in four treatments: DC - control diet; DG - glutamine diet (1% L-glutamine + glutamic acid); DA - arginine diet (1% L-arginine); and DGA - glutamine + arginine diet (0.5% L-glutamine + glutamic acid and 0.5% L-arginine) with eight replicates and two animals per experimental unit. The addition of 1% L-arginine to the piglet diet improved weight gain and feed conversion over 28 to 35 days of age. In the period of 28 to 49 days of age, supplementation with 1% L-glutamine + glutamic acid increased the animals’ weight gain and reduced the incidence of diarrhea. Supplementation with amino acids in combination had a positive effect on the morphometric parameters of the intestinal mucosa compared to the control diet. Supplementation with 1% L-glutamine + glutamic acid increased the number of anti-PCNA+ cells and goblet cells. Taken together, our findings suggest that supplementation with L-glutamine + glutamic acid and L-arginine can improve the productive performance and enhance the integrity of the intestinal mucosa of weaned piglets.